34.3k views
5 votes
So Confused!! Somebody Plz Explain How To Do!!!!!!!

For the following system, use the second equation to make a substitution for y in the first equation.

3x + y = 1
y + 4 = 5x

What is the resulting equation?

A.) 3x + 5x - 4 = 1
B.) 3x + 4 - 5x = 1
C.) 3x + 5x + 4 = 1

1 Answer

5 votes

Answer: A) 3x + 5x - 4 = 1

Explanation:

The second equation is y + 4 = 5x. Solve this equation for y by subtracting 4 from both sides. --> y = 5x - 4

Now replace "y" in the first equation with "5x - 4".

3x + y = 1

--> 3x + (5x - 4) = 1

User Cer
by
6.4k points